2007
DOI: 10.1152/ajprenal.00139.2006
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin metabolism in renal proximal tubules, urine, and serum of sheep: evidence for ACE2-dependent processing of angiotensin II

Abstract: Despite the evidence that angiotensin-converting enzyme (ACE)2 is a component of the reninangiotensin system (RAS), the influence of ACE2 on angiotensin metabolism within the kidney is not well known, particularly in experimental models other than rats or mice. Therefore, we investigated the metabolism of the angiotensins in isolated proximal tubules, urine, and serum from sheep. Radiolabeled [125 I]ANG I was hydrolyzed primarily to ANG II and ANG-(1-7) by ACE and neprilysin, respectively, in sheep proximal tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
151
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 38 publications
(45 reference statements)
6
151
1
Order By: Relevance
“…Recent studies confirmed that NEP can metabolize Ang I directly into Ang-(1-7), and, furthermore, NEP can act upon Ang II to yield Ang-(1-4) and Ang-(3-4), but not Ang-(1-7) in sheep renal proximal tubular membranes (Shaltout et al 2007). …”
Section: Neprilysin 2411mentioning
confidence: 93%
“…Recent studies confirmed that NEP can metabolize Ang I directly into Ang-(1-7), and, furthermore, NEP can act upon Ang II to yield Ang-(1-4) and Ang-(3-4), but not Ang-(1-7) in sheep renal proximal tubular membranes (Shaltout et al 2007). …”
Section: Neprilysin 2411mentioning
confidence: 93%
“…28,29 Besides, kinetic differences in AngI and AngII metabolism are shown to be exist between rat, human and sheep kidneys. 25,30,31 There are some limitations to our study. First, our data were obtained in adult animals with established hypertension and hence do not rule out a role for renal ACE2 in the early onset of hypertension.…”
Section: Controlsmentioning
confidence: 97%
“…It is widely accepted that small peptides derived from Ang Ⅱ have local physiological effects, especially in the kidney (Figure 1). ACE2 is a transmembrane glycoprotein that shares a 42% of homology with ACE and contains a single active site domain more closely to the N domain of ACE [16,38] . Unlike ACE, ACE2 is a monocarboxypeptidase, generating Ang-(1-7) by the cleavage of a single Phe residue from Ang Ⅱ, and Ang-(1-9), removing the C-terminal Leu residue from Ang Ⅰ [16,38] .…”
Section: New Members Of Ras: Ang Ii-derived Peptidesmentioning
confidence: 99%
“…ACE2 is a transmembrane glycoprotein that shares a 42% of homology with ACE and contains a single active site domain more closely to the N domain of ACE [16,38] . Unlike ACE, ACE2 is a monocarboxypeptidase, generating Ang-(1-7) by the cleavage of a single Phe residue from Ang Ⅱ, and Ang-(1-9), removing the C-terminal Leu residue from Ang Ⅰ [16,38] . Within the renal brush-border vesicles of the rat, Ang-(1-7) is preferentially hydrolyzed by aminopeptidases and neprylisin (NEP) after aminopeptidase blockade, generating Ang-(1-4) [39] .…”
Section: New Members Of Ras: Ang Ii-derived Peptidesmentioning
confidence: 99%
See 1 more Smart Citation